Rebecca of Sunnybrook Farm - Wiggin, Eric E. (Wolgemuth & Hyatt, 1991)
At seventeen, Rebecca inherits her Aunt Miranda's estate and she has high hopes of turning it into a working farm, taking care of her large family, and getting to know railroad executive Adam Ladd even better.